2022
DOI: 10.1002/ejic.202200295
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorescent Cyclometalated Platinum(ii) Hexahydroimidazo[1,5‐a]pyridinylidene Complexes

Abstract: The synthesis of N-heterocyclic carbene precursors based on the hexahydroimidazo[1,5-a]pyridine and their corresponding cyclometalated platinum(II) carbene complexes is reported. All compounds are fully characterized by standard techniques and additionally X-ray structures could be obtained for three complexes. The photophysical properties of these platinum complexes were investigated by absorption and photolumines-cence measurements. All complexes showed strong phosphorescence at room temperature in the sky-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Computational results suggest that this signal is attributed to the LUMO on the β-diketonate. [84,87,88] Then, at higher voltage, multiple irreversible events take place. A characteristic signal for this class of platinum(II) complexes with fluorene or xanthene scaffolds as part of the C^C*-ligand (Scheme 1) is found at À 2.9 V. [84] A similar voltammogram with multiple events at higher voltage (from À 2.9 V) was recorded for complex 6.…”
Section: Cyclovoltammetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Computational results suggest that this signal is attributed to the LUMO on the β-diketonate. [84,87,88] Then, at higher voltage, multiple irreversible events take place. A characteristic signal for this class of platinum(II) complexes with fluorene or xanthene scaffolds as part of the C^C*-ligand (Scheme 1) is found at À 2.9 V. [84] A similar voltammogram with multiple events at higher voltage (from À 2.9 V) was recorded for complex 6.…”
Section: Cyclovoltammetrymentioning
confidence: 99%
“…This effect is often observed for the mesacac ligand, but still lacks a reliable explanation. [17,[85][86][87][88] Recently, we found that the cyclometalating fluorene motif of the SBF building block is able to neutralize the influence on the photophysical properties of the mesacac auxiliary ligand. [84] By synthesizing the corresponding regioisomers of the 2'-SFX complexes, we obtained an ideal platform for the rigorous study of this effect.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In particular, cyclometalating variants of these ligands, in which at least one of the pyridine rings is replaced by a phenyl one, have attracted chemistry, [34][35][36] but also with respect to opto-electronic applications Pt(II) complexes with NHC ligands have been studied. [37] In this respect, the NHC moiety might either represent a monodentate ligand [35,38] or be a part of a bidentate, [39][40][41][42][43] tridentate [44][45] or even tetradentate ligand framework. [46][47] In the overwhelming majority of the published studies imidazole or one of its derivatives (e. g., benzo[d]imidazole) is employed as the NHC precursor.…”
Section: Introductionmentioning
confidence: 99%
“…We as well as other research groups have established a class of such ligands in emissive transition metal complexes in the past decade, namely cyclometalated N -heterocyclic carbene (C^C*) ligands. , As derivatives of the more common 2-phenylpyridines (C^N), the C^C* ligands help to facilitate more energy-rich emissions due to the stronger donor effect of the carbene motif. In addition to the extensive variation of the cyclometalated NHC ligands, we investigated the influences of different auxiliary ligands on the emission properties of emissive platinum(II) complexes in several studies. More recently, we successfully used bis(pyrazolyl)borate ligands as auxiliary ligands, resulting in excellent phosphorescent platinum emitters. , To further explore the applicability of borate ligands in photophysically active complexes, we chose to use bis(pyridyl)borate ligands. Transition metal complexes with bis(pyridyl)borates and tris(pyridyl)borates have been known for more than 20 years.…”
Section: Introductionmentioning
confidence: 99%